Enhancing Middle School Students’ Narrative Writing through Video-Based Instruction - Sahabuddin, Ilham; Wahyuddin; Khadijah Maming; Hasman (Journal of Applied Linguistics, 2025)
This study investigated the use of video as a medium to improve eighth-grade students’ narrative writing ability and interest. Using a quasi-experimental design with pre-tests and post-tests, two classes (experimental and control), each consisting of 30 students, were selected through cluster random sampling at SMP Negeri 2 Parepare. Writing tests and questionnaires were employed for data collection. Results showed that the experimental class outperformed the control class, with post-test mean scores of 74.30 and 69.80, respectively. Questionnaire results also indicated a high level of student interest (82.30). A t-test confirmed a significant difference between the classes (t-test = 2.18 > t-table = 2.00), supporting the hypothesis. The findings suggest that video effectively enhances students’ narrative writing ability and interest. Keywords : Video-Based Instruction; writing; narratives text